Penerapan metode Value chain dan Four Stage Life Cycle untuk menentukan kandidat aplikasi pada Laboratorium ITCC STT-PLN: Hendra Jatnika, Luqman, Dewi Arianti Wulandari - Jurnal, Redaksi Tim (PETIR, 2018)
Strategies and policies in a profit oriented organization also have a social mission (public service) that prioritizes customer service. The development of information systems and information technology will have an impact on the increasingly competitive competition, this is true also in the world of seretifikasi demands the manager to build and develop information systems in helping business activities, achieve organizational goals and services for stakeholders, especially those related to data, information , technology and application, found some cases of information system management failure in achieving organizational goals (objective) because the utilization is not in accordance with the direction and objectives of the organization Value added chain method, which is to describe how to see the business as a chain of activities that change input to output while Four Stage Life Cycle Business System Planning (BSP) is a tool used to determine the derivatives of business functions and application candidates associated with the products / services provided by business functions. ITCC (Information Technology Certification Center) STT PLN is a laboratory that handles several certification programs both international scale, it is necessary to align the utilization of information systems and information technology in accordance with the direction and purpose of college, so that required application and technology and implementation plan of the architecture has been created to support business activities for the achievement of the organization's mission.